Aryojeding Rejotangan Tulungagung: Investigation of an Oral Literature using Van Perseun's Theory of Culture: Situs Aryojeding Rejotangan Tulungagung: Penelusuran sebuah Sastra Lisan Perspektif Teori Kebudayaan Van Perseun - Etsha Ari Kusuma Dianti; Novi Siti Kussuji Indrastuti (Lakon : Jurnal Kajian Sastra dan Budaya, 2024)
The aim of this research is to uncover the cultural phases of the Aryojeding site in Rejotangan, Tulungagung, through the lens of Van Perseun's cultural theory. There are two nearby relics at the site: the tomb of Ki Ageng Sengguruh and the Aryojeding temple or shrine. The research method employed is qualitative-descriptive.The findings reveal mystical elements, evident in myths and food-related artifacts. Ontological studies highlight traditions such as pilgrimage and the slametan ritual during the Satu Suro (Javanese New Year). From a functional perspective, the community regards this tomb as both a historical source and a cultural heritage asset worth preserving, leading to its designation as a "site" that is part of a protected cultural reserve. Additionally, the site has a caretaker (juru kunci), reinforcing its functional phase as an educational medium.